Gravitational Wave Astrophysics : Proceedings of the Third Session of the Sant Cugat Forum on Astrophysics - Sopuerta, Carlos F. (Astrophysics and Space Science Proceedings,, 2015)
This book offers review chapters written by invited speakers of the 3rd Session of the Sant Cugat Forum on Astrophysics - Gravitational Waves Astrophysics. All chapters have been peer reviewed. The book goes beyond normal conference proceedings in that it provides a wide panorama of the astrophysics of gravitational waves and serves as a reference work for researchers in the field.